Sounding out ethnography and design: developing metadata frameworks for designing personal heritage soundscapes - Chamberlain, Alan; Bødker, Mads; Papangelis, Konstantinos (Audio Engineering Society, 2018)
The paper presents reflections on understanding the issues of designing locative sonic memory-scapes. As physical space and digital media become ever more intertwined, together forming and augmenting meaning and experience, we need methods to further explore pos- sible ways in which physical places and intangible personal content can be used to develop meaningful experiences. The paper explores the use of autoethnography as a method for sound- scape design in the fields of personal heritage and locative media. Specifically, we explore possible connections between digital media, space, and “meaning making,” suggesting how autoethnographies might help discover design opportunities for merging digital media and places. These are methods that are more personally relevant than those typically associated with a more system-based design approaches that we often find are less sensitive to the way that emotion, relationships, memory, and meaning come together. As a way to expand upon these relationships we also reflect on relations between personal and community-based responses.